2005
DOI: 10.1523/jneurosci.5170-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Apolipoprotein E4 Alters the Amyloid-β 40:42 Ratio and Promotes the Formation of Cerebral Amyloid Angiopathy in an Amyloid Precursor Protein Transgenic Model

Abstract: Alzheimer's disease (AD) is characterized by the aggregation and deposition of the normally soluble amyloid-␤ (A␤) peptide in the extracellular spaces of the brain as parenchymal plaques and in the walls of cerebral vessels as cerebral amyloid angiopathy (CAA). CAA is a common cause of brain hemorrhage and is found in most patients with AD. As in AD, the ⑀4 allele of the apolipoprotein E (apoE) gene (APOE) is a risk factor for CAA. To determine the effect of human apoE on CAA in vivo, we bred human APOE3 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
202
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(226 citation statements)
references
References 50 publications
19
202
3
2
Order By: Relevance
“…A fifty percent reduction of ApoE also decreased CAA (45). In contrast, when human ApoE4 is overexpressed in Tg2576 mice, the distribution of amyloid pathology is altered in favor of vascular vs. parenchymal deposits (46). In the present study, we found that apocynin and, to a lesser degree, tempol decrease mouse ApoE levels-an effect that would be expected to decrease CAA formation to a far greater extent than neuritic plaques.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…A fifty percent reduction of ApoE also decreased CAA (45). In contrast, when human ApoE4 is overexpressed in Tg2576 mice, the distribution of amyloid pathology is altered in favor of vascular vs. parenchymal deposits (46). In the present study, we found that apocynin and, to a lesser degree, tempol decrease mouse ApoE levels-an effect that would be expected to decrease CAA formation to a far greater extent than neuritic plaques.…”
Section: Discussionsupporting
confidence: 43%
“…Taken together, these findings represent direct evidence that ROS play a causal role in the CV deficits induced by fibrillar Aβ in the form of CAA and that the source of the ROS is likely NADPH oxidase. In addition, we provide preliminary evidence that one mechanism by which ROS impact CAA pathogenesis is via an effect on ApoE-a factor known to promote CAA formation (45,46). Our findings have both mechanistic and therapeutic significance.…”
Section: Discussionmentioning
confidence: 56%
“…E2) Ito et al 2007;Deane et al 2008). In addition, apoE can influence the pathogenesis of CAA in an amyloid protein precursor (APP)-transgenic mouse model, with apoE4 increasing the amount of vascular plaques in comparison to apoE3 (Fryer et al 2005b In vitro and in vivo data including data in humans and animal models suggests that the physical interaction of apoE with Ab plays an important role in AD and CAA pathogenesis (Fig. 1).…”
Section: Genetic Clinical and Biomarker Observations On Relationshimentioning
confidence: 99%
“…In addition, the anatomical pattern of Ab deposition differs in the absence of apoE (Holtzman et al 2000a;Irizarry et al 2000). The expression of human apoE isoforms in either PDAPP or Tg2576 Tg mice resulted in a marked delay in the deposition of Ab and formation of neuritic plaques, compared with APP Tg mice expressing no apoE or mouse apoE Fryer et al 2005b). Importantly, expression of human apoE isoforms in APP Tg mice results in an isoform-specific effect on the amount of Ab accumulation as well as true amyloid deposits (E4 .…”
Section: Genetic Clinical and Biomarker Observations On Relationshimentioning
confidence: 99%
See 1 more Smart Citation